Analysis of trust and social participation network among activists of sericulture in Guilan Province, Northwestern Iran and sustainable development in sericulture industry using Ucinet software - Mohammad Karim Motamed; Reza Esfanjari Kenari; Fatemeh Ghorbani Piralidehi; Vahid Sheidadoost (Caspian Journal of Environmental Sciences)
Trust and social participation are the basic prerequisites for achieving sustainable agricultural development, which creates sustainable employment, sustainable income and empowerment of the rural community. Sericulture is an important tool in achieving sustainable development in such societies, and in this regard, the position of the network of activists is important. This study has been conducted with the aim of analyzing the network of social trust and participation among activists of sericulture in Guilan Province, Northwestern Iran to achieve sustainable agricultural development. The statistical population was composed of two groups. The first included 7310 silk farmers in 16 counties of the province out of them, 365 farmers were selected by simple randomization. The second included 12 sericulture activists whose work activity was related to the sericulture industry of the province. A questionnaire was the main research instrument whose validity was examined by a panel of 15 experts and university teachers and its reliability was estimated at 0.81 by Cronbach’s alpha. The results showed that most silk farmers report their social trust at low level, while their social participation at moderate. The analysis of other sericulture activists reveals that the coherence and stability of social trust are at moderate level, while the coherence of the participation network is at weak level and its stability is at good level. Agriculture-Jahad Organization in Iran is also the most trusted activists in the social trust and participation network of silk farmers as it has the highest in-degree centrality, whereas the activists express that the cocoon-drying factory and the silk-extraction factory are at the lowest level among the activists of the trust network, while the silk extraction factory and the private service sector are at the lowest level in the participation network.